PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Made Widya Sari; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
This research strives to find out Corporate governance, Company Size, and Leverage to The Company's Value. This research was conducted at the Indonesia Stock Exchange, with research objects of food and beverage sector manufacturing companies in the period 2016-2018. Determination of samples in this study was done by purposive sampling techniques Data analysis techniques used are multiple linear regression analysis. In addition, in this study also conducted descriptive statistic analysis as well as classical assumption test. The test results showed that partially the variables of corporate governance had a negative and significant effect on the company's value in the food and beverage sector. The Company's size has an insignificant positive effect on the company's value in the food and beverage sector. Leverage has a positive and significant effect on the company's value in the food and beverage sector. As well as the results of simultaneous testing shows that Corporate governance, company size, and Leverage simultaneously have a significant effect on the company's value in the food and beverage sector.